STUDY OF MULTI-STAGE SATELLITE LAUNCH VEHICLE PROPULSION SPECIFICATIONS DETERMINATION BASED ON ASCENT PROBLEM - Fariz (13613032), Ahmad
In this final project, a study of ascent problems in the conceptual design of satellite launch vehicle was done. The sub-problems studied were about the selection of trajectories and the selection of rocket propulsion. The reference trajectory is the optimal trajectory, which is the solution of optimization two-point boundary value problem. The reference trajectory is related to the acceleration profile and thrust required, where the thrust profile required will become the baseline of specifying the propulsion specification of each stage in multi-stage rocket. To carry out the selection of propulsion, a test platform of rocket flight with specific propulsion specifications was built using the MATLAB code. Then a flight simulation platform was built to test flight performance of the rocket designed. To optimize the rocket trajectory, the time of the coast was applied in its flight. The deviations about the reference trajectory and the final orbital conditions underlie the use of a simple feedback control system. The case studied in this final project was a 3-stages satellite launch vehicle with mass referring to a research done by Utama [1]. The design boundary conditions refer to the LAPAN satellite launch vehicle roadmap that targets 3 stages rocket to launch a 50 kg satellite to the Low Earth Orbit 200 km [2]. Materials/data to select rocket propulsion specifications derived from launch vehicles with similar specification that had already operated in the world. The process done in this final project shown that the satellite launch vehicle trajectories of the rocket designed approximated the altitude of orbit when using coast time and control systems. However, lack of energy becomes a problem to achieve speed and centripetal acceleration in orbit.